Basil Bernstein : the thinker and the field - Moore, Rob, 1946- (Routledge, 2013)
"Basil Bernstein: the Thinker and the Field provides a comprehensive introduction to the work of Basil Bernstein, demonstrating his distinctive contribution to social theory by locating it within the historical context of the development of the sociology of education and Sociology in Britain. Although Bernstein had a particular interest in education, he did not see himself as a sociologist of education alone. By exploring Bernstein's intellectually collaborative character and the evolving system of ideas, drawing upon anthropology and linguistics, the originality of Bernstein's contribution to the social sciences can be truly identified. Rob Moore's text offers a provocative and challenging account both of Bernstein, and of British sociology and education, approaching Bernstein's work as a complex model of intertwining ideas rather than a single theory. Continued interest in Bernstein's work has opened up a world-wide network of scholarship, and Moore considers contemporary research alongside classical sources in Durkheim and Marx, to provide a historical analysis of the fields of British Sociology and the sociology of education, pinpointing Bernstein's position within them. The book is organised into two main parts: The Field Background and Beginnings Durkheim, Cosmology and Education The Problematic The Structure of Pedagogic Discourse Bernstein and Theory Bernstein and research The Pedagogic Device Written by a leading authority in the field, this text will be valuable reading for post-graduate students of sociology and education, along with active researchers and their research students"--